Effect of acidic beverages on surface roughness and color stability of artificial teeth and acrylic resin - Bitencourt, Sandro Basso [UNESP]; Catanoze, Isabela Araguê [UNESP]; da Silva, Emily Vivianne Freitas [UNESP]; dos Santos, Paulo Henrique [UNESP]; dos Santos, Daniela Micheline [UNESP]; Turcio, Karina Helga Leal [UNESP]; Guiotti, Aimée Maria [UNESP] (XMLink, 2020)
PURPOSE. The aim was to evaluate the effect of four acidic beverages on the roughness (Ra) and color change (ΔEab) of two brands of artificial teeth and a heat-polymerized acrylic resin (HPAR) for use in a prosthetic base. MATERIALS AND METHODS. All materials were divided into 5 groups, according to the used acidic beverage (artificial saliva-control, red wine, orange juice, coke-based, and lemon juice-based soft drink). The immersion process was divided into two stages: T1-immersion in the acidic solutions for 10 minutes for 14 days; T2-after T1, the samples were immersed in grape juice for 14 days. The Ra of the samples was evaluated in a rugosimeter and the ΔEab in a spectrophotometer, before and after the immersions. The analysis of variance of one (ΔEab) and two factors (Ra) and Tukey were performed (α=.05). RESULTS. There was a statistical difference for roughness after immersion (T1) for Trilux and Tritone teeth, regardless of the acid solution. For Trilux teeth, all acid solutions increased Ra (P<.05). For Tritone teeth, only the coke-based soft drink did not statistically change Ra. Grape juice (T2) altered Ra only of artificial teeth (P<.05). The color was changed for all materials, after T1 and T2. CONCLUSION. In general, the acidic solutions changed the Ra and ΔEab of HPAR and artificial teeth after T1. The grape juice altered the roughness only of the artificial teeth, promoting a clinically acceptable color change in the materials.
Keywords: Acrylic resins; Artificial teeth; Color; Physical properties; Surface analysis